Navigating Educational Challenges in Indonesia: Strategic Planning for Sustainable Education Inspired by Philip H. Coombs - Nurhasanah, Siti; Suyatman, Ujang (Jurnal Manajemen Pendidikan : Jurnal Ilmiah Administrasi, Manajemen dan Kepemimpinan Pendidikan, 2025)
This study examines the educational challenges and opportunities within Indonesia's educational system, drawing on the foundational insights of Philip H. Coombs and his emphasis on strategic educational planning. Set against the backdrop of demographic shifts and increasing demands for equitable access, the research aims to identify strategies for fostering sustainable education. Utilizing a literature review, the study synthesizes existing research on educational policies, demographic trends, and technological advancements. Findings highlight significant progress in curriculum development and technology integration yet underscore persistent challenges such as teacher shortages and resource disparities across regions. The analysis reveals that public-private partnerships and community involvement are crucial for bridging funding gaps and enhancing infrastructure. Coombs' principles of aligning educational goals with society needs are particularly relevant, emphasizing the need for a balanced approach that integrates both quantitative expansion and qualitative enhancement. The study concludes that effective policy and leadership are vital for sustainable educational planning, requiring inclusive and adaptable strategies that reflect Indonesia's diverse cultural and geographic landscape. Future research should focus on assessing the long-term impacts of technological solutions and developing incentive models for educator retention in underserved areas. This research underscores the importance of collaboration among stakeholders to create an educational system that is resilient, equitable, and prepared for future challenges.